Financial technology (FinTech) as a financial development factor in the EU countries - Olga Lavrinenko; Edmunds Čižo; Svetlana Ignatjeva; Alina Danileviča; Krzysztof Krukowski (Economies, 2023)
The aim of the research is to determine the impact of financial technology (FinTech) on financial development in EU countries. The multi-dimensional nature of the concepts described above and the low availability of data for regions smaller than countries makes it difficult to investigate the link between financial development and FinTech, as well as affects the values of the results due to a certain averaging of indices across countries. The study examines the Global FinTech Index and the Financial Development Index, which characterize financial development in the EU countries, as well as the sub-indices of the Financial Development Index. The article applies frequency analysis and correlation analysis methods. A positive linear relationship between the Global Fintech Index and the Financial Markets Index sub-index, as well as its components Financial Markets Depth Index and Financial Markets Efficiency Index, has been identified. There is also a positive linear relationship between the Global FinTech Index and the Financial Institutions Depth Index, while a negative linear relationship has been identified between the Global FinTech Index and the Financial Institutions Access Index.
Keywords: 330; EU; financial development; financial technology (FinTech)